ANALYSIS OF CHEMICAL COMPOSITION BY GC/MS AND ASSESSMENT OF ANTICANCER ACTIVITY OF RHUBARB (Rheum ribes Linn.) STALKS (Applied Biological Research, 2023)
Rheum ribes Linn. (Polygonaceae) is an important medicinal plant  abundantly growing in Iraqi Kurdistan. In Kurdish society this plant is  traditionally used as laxative for the treatment of constipation. The aim of  present study was to characterize the chemical compounds present in the ethanolic extract of R. ribes and evaluate its anticancer activity. The  chemical characterization of ethanolic extract of R. ribes was done by GC/ MS. Its anticancer activity was determined by MTT assay using human  breast cancer (MCF-7) cell lines. Sixty-two chemical compounds were  identified by GC/MS analysis. Hexatriacontane (11.2%), heptadecane 2,6,10,15-tetramethyl (5.53%), 7-hexadecenal, (z)- (4.63%), vitamin E  (3.85%), 3,7,11,15-tetramethylhexadec-2-en-1-yl dodecanoate (3.67%), and tetratriacontane (3.65%) were observed as the major chemical compounds  in the ethanolic extract. The ethanolic extract showed a time- and  concentration-dependent cytotoxicity with IC50 value of 312.31 ± 4.19 µg mL-1. The present study revealed the anticancer potential of R. ribes extract  and provides a scientific basis for its possible use as anticancer remedy.
Keywords: Breast cancer; GC/MS analysis; Rheum ribes; MTT assay